ANALISIS PRIMER UNTUK AMPLIFIKASI PROMOTER inhA MULTIDRUG RESISTANCE TUBERCULOSIS (MDR-TB) DENGAN METODE POLYMERASE CHAIN REACTION (PCR) - Agung Septiari, I Gusti Ayu; Sanna Yustiantara, Putu; Chandra Yowani, Sagung (Jurnal Kimia (Journal of Chemistry), 2015)
The aim of this study was to analyze several primary combinations for amplifying inhA promoter region by in silico and in vitro ways. Primary in silico ’s analysis was done by Clone Manager Suite 6 program. fabG gene sequence of M. tuberculosis was downloaded from www.ncbi.nlm.nih.gov (genbank: U66801.1) and used as DNA template. In vitro detection was done by PCR technique using P16 and 86 M. tuberculosis MDR isolates as DNA template. Amplification was done in described conditions: predenaturation at 95°C for 15 minutes, 45 cycle of amplication (denaturation on 94°C for 1 minute, annealing on 54°C for 1 minute 20 seconds dan extension on 72°C for 1 minute 10 seconds) and also post extension on 72°C for 10 minutes. PCR product was detected by agarose gel elektroforesis (1,5%). In conclusion, combination of primary forward (mabA-inhA-promoter-FS) 5’-ACATACCTGCTGCGCAAT-3’ (18 nucleotide) and primary reverse (mabA-inhA-promoter-R) 5’-CTCCGGTAACCAGGACTGAA-3’ (20 nucleotide) (Chen et al. , 2011) have met the good criteria of primary combination which was seen from several aspects such as: primary length, Tm value, %GC, stability, number of hairpins , dimers and runs . In vitro detection showed that the primary combination also amplified inhA promoter region with the length of 284 pb
Keywords: Primer analysis, PCR, inhA promoter region, M. tuberculosis, in silico, in vitro, Clone Manager Suite 6